1991
DOI: 10.1073/pnas.88.5.1913
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione deficiency leads to mitochondrial damage in brain.

Abstract: Glutathione deficiency induced in newborn rats by giving buthionine sulfoximine, a selective inhibitor of y-glutamylcysteine synthetase, led to markedly decreased cerebral cortex glutathione levels and striking enlargement and degeneration ofthe mitochondria. These effects were prevented by giving glutathione monoethyl ester, which relieved the glutathione deficiency, but such effects were not prevented by giving glutathione, indicating that glutathione is not appreciably taken up by the cerebral cortex. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(197 citation statements)
references
References 50 publications
(58 reference statements)
6
190
0
1
Order By: Relevance
“…1B). Treatment with 40 μg/ml dox for 24 h resulted in a decrease in GSH levels of approximately 50%, a similar decrease to that previously reported to occur in the SN of early PD brains [2,5]. Consequently, this dosage regime was used for all subsequent experiments.…”
Section: Generation Of N27 Anti-gcl Cells With Inducibly Reduced Gcl supporting
confidence: 68%
See 1 more Smart Citation
“…1B). Treatment with 40 μg/ml dox for 24 h resulted in a decrease in GSH levels of approximately 50%, a similar decrease to that previously reported to occur in the SN of early PD brains [2,5]. Consequently, this dosage regime was used for all subsequent experiments.…”
Section: Generation Of N27 Anti-gcl Cells With Inducibly Reduced Gcl supporting
confidence: 68%
“…GSH is synthesized in the cytosol and transported into the mitochondria via an energy-dependent transporter. Decreased GSH availability in the brain has been demonstrated to promote morphological mitochondrial damage [5]. We have previously demonstrated that GSH depletion via downregulation of GCL activity in dopaminergic cells in vitro results in a rather selective inhibition of CI activity which is rate-limiting with regard to mitochondrial function [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione is also essential for maintenance of the thiols of proteins and of other antioxidants, for example, ascorbate and α -tocopherol (18,19). A decreased glutathione level, through inhibition of its synthesis, is accompanied by increased excitotoxic response to NMDA, degeneration of mitochondria, and larger infarct areas in stroke models (20)(21)(22). Extracellularly, glutathione has been suggested to have multifaceted electrophysiological effects by binding to its own receptors and by modulating glutamatergic excitatory neurotransmission by displacing glutamate from its ionotropic receptors (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Brain GSH depletion leads to increased productions of superoxide, hydroxyl radicals, and H 2 O 2 (13). Treatment with Lbuthionine sulfoximine (BSO) a specific inhibitor of glutamate-cysteine ligase (GCL), the rate-limiting enzyme of GSH biosynthesis, leads to GSH depletion (14). Decreased intracellular GSH due to BSO treatment worsened oxidative damage in vivo (15), while increased intracellular GSH due to n-acetylcysteine (NAC) treatment ameliorated this damage (16).…”
Section: Oxidative Stress In the Central Nervous Systemmentioning
confidence: 99%